2020
DOI: 10.4102/hsag.v25i0.1473
|View full text |Cite
|
Sign up to set email alerts
|

A road less travelled: Undergraduate midwifery students’ experiences of a decentralised clinical training platform

Abstract: Background: In South Africa, the critical skill base shortage of healthcare workers, the underperforming global health indicators and the planned roll out of the National Health Insurance have burdened South African higher education authorities to rapidly expand nursing student enrolments. The expansion in student numbers has placed increased demands on overstretched educational institutions, and students are confronted with challenges of congestion in classrooms and clinical facilities, while lecturers encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…CPDs are mandatory across the globe to enhance competent, effective, and quality health care delivery [4,5]. The findings of this study are in agreement with those of [38] in their review of a five-year's literature and professional web search on mandatory CPDs. The Engagement of nurses and midwives in CPDS was found to be less.…”
Section: Discussionsupporting
confidence: 87%
“…CPDs are mandatory across the globe to enhance competent, effective, and quality health care delivery [4,5]. The findings of this study are in agreement with those of [38] in their review of a five-year's literature and professional web search on mandatory CPDs. The Engagement of nurses and midwives in CPDS was found to be less.…”
Section: Discussionsupporting
confidence: 87%
“…We will address the initial research inquiry about students' knowledge of clinical nursing training by consulting Tables 2 and 3 In juxtaposition to our research outcomes, Fakude (2018) conducted an exploratory design study, examining the perspectives of lecturers, clinical supervisors, and student nurses within an undergraduate nursing program at a South African university in the Western Cape. Their finding revealed a notably contrasting position, wherein many nursing students harbored unfavorable perceptions of their clinical nursing training.…”
Section: Discussionmentioning
confidence: 99%
“…However, for therapeutics privileges, there remain limited opportunities for meeting the minimum HPCSA requirements for registration within the tertiary institutions and in the private sector, hence the importance of decentralising clinical training to the public sector. 8 At one of the South African institutions, which was the first to implement DCT in the undergraduate clinical training of optometry in the year 2016, final-year students enrolled in the Clinical Grand Rounds module at that institution and completed a 3-week block placement at different public health facilities. The Clinical Grand Rounds module builds on the theoretical and practical knowledge obtained in the first semester modules of general clinics (analogous to primary care clinics), binocular vision (BV), contact lenses (CL), paediatric vision (PV) and low vision (LV) in providing clinical training experience in all components.…”
Section: Introductionmentioning
confidence: 99%
“…Positive learning experiences at decentralised training platforms have been noted in the discipline of nursing, including areas of competency, personal growth and confidence, mutual benefit to students and the health care system. 8,9 Resource limitations including access to Wi-Fi did pose a challenge to functioning in a clinical setting and as a student, with a perception of lack of support from clinical tutors also noted. 8,9 From the perspective of supervising optometrists, Ebrahim et al 2 reported support for the DCT model by public sector optometrists despite envisaged challenges such as limited resources and lack of formal training to fulfil the role of clinical educators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation